2011
DOI: 10.1111/j.1369-1600.2010.00311.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin attenuates the expression of cocaine‐induced place preference and behavioral sensitization

Abstract: The mammalian target of rapamycin (mTOR) is a serine-threonine kinase that controls global protein synthesis, in part, by modulating translation initiation, a rate-limiting step for many mRNAs. Previous studies implicate mTOR in regulating stimulant-induced sensitization and antidepressive-like behavior in rodents, as well as drug craving in abstinent heroin addicts. To determine if signaling downstream of mTOR is affected by repeated cocaine administration in reward-associated brain regions, and if inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 46 publications
1
55
0
Order By: Relevance
“…Both acute systemic and intra-NAC injections of rapamycin attenuated alcohol-drinking behaviors and conditioned place preference (CPP) for alcohol (Neasta et al, 2010). Acute systemic rapamycin treatment also suppressed the expression of cocaine CPP, behavioral sensitization to cocaine (Bailey et al, 2012), and the sensitization of meth-amphetamine CPP (Narita et al, 2005). These findings indicate that mTORC1 may have a role in controlling the processes responsible for the strengthening of drug/cue associations.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Both acute systemic and intra-NAC injections of rapamycin attenuated alcohol-drinking behaviors and conditioned place preference (CPP) for alcohol (Neasta et al, 2010). Acute systemic rapamycin treatment also suppressed the expression of cocaine CPP, behavioral sensitization to cocaine (Bailey et al, 2012), and the sensitization of meth-amphetamine CPP (Narita et al, 2005). These findings indicate that mTORC1 may have a role in controlling the processes responsible for the strengthening of drug/cue associations.…”
Section: Introductionmentioning
confidence: 69%
“…rapamycin reduced lever pressing for cocaine when PR conditions were required to obtain cocaine infusions. To date, data supporting the role for mTORC1 in psychostimulant reinforcement has been limited to CPP and sensitization studies (Bailey et al, 2012;Narita et al, 2005). However, mTORC1 inhibition has been reported to reduce low-effort alcohol drinking in mice and FR1 alcohol self-administration in rats (Neasta et al, 2010).…”
Section: Intra-cerebroventricular Mtorc1 Inhibition Reduces Pr Responmentioning
confidence: 99%
“…Several studies have reported that rapamycin can inhibit drug-seeking in animals and drug-craving in humans after withdrawal. On the other hand, memory retrieval is usually completely impaired by protein synthesis inhibitors (Shi et al, 2009;Neasta et al, 2010;Wang et al, 2010;Bailey et al, 2012;Dayas et al, 2012). Rapamycin, an inhibitor of mTOR, frequently used in organ transplantation to prevent rejection via the inhibition of protein synthesis, can successfully enter the brain in rats and humans.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to well-established roles for NMDA receptors and downstream signaling pathways (Torregrossa and Taylor, 2013), de novo protein synthesis is necessary for retrieval and/or reconsolidation of cocaine memories (Lee et al, 2006;Fuchs et al, 2009;Fan et al, 2010;Théberge et al, 2010;Bailey et al, 2012;Ren et al, 2013;Shi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%